2020
DOI: 10.3389/fphar.2020.01065
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside Protected Against Oxidative Stress-Induced Liver Injury via the PHLPP2-AKT-GSK-3β Signaling Pathway In Vivo and In Vitro

Abstract: Hyperoside, isolated from Drosera rotundifolia L., seeds of Cuscuta chinensis Lam., or Hypericum perforatum L., originally showed to possess an antifungal and antibacterial activity, while recently showed the protective effects against oxidative stress-induced liver injury. This study investigated such a protective effect of hyperoside and the underlying molecular mechanisms in vitro and in carbon tetrachloride (CCl4)-injured rat livers. The data showed that hyperoside was able to prevent the oxidative stress-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…On the contrary, reports have demonstrated that inhibitory phosphorylation of GSK‐3β at Ser9 by the Ser/Thr kinase protein, p‐Akt (Ser473), enhances Nrf2 nuclear accumulation 15 . Upregulation of the Akt (Ser473)/GSK‐3 (Ser9)/Fyn/Nrf2 axis has been shown to alleviate oxidative stress‐induced liver injury and myocardial infarction and cardiotoxicity 17–19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, reports have demonstrated that inhibitory phosphorylation of GSK‐3β at Ser9 by the Ser/Thr kinase protein, p‐Akt (Ser473), enhances Nrf2 nuclear accumulation 15 . Upregulation of the Akt (Ser473)/GSK‐3 (Ser9)/Fyn/Nrf2 axis has been shown to alleviate oxidative stress‐induced liver injury and myocardial infarction and cardiotoxicity 17–19 …”
Section: Introductionmentioning
confidence: 99%
“…15 Upregulation of the Akt (Ser473)/GSK-3 (Ser9)/Fyn/Nrf2 axis has been shown to alleviate oxidative stress-induced liver injury and myocardial infarction and cardiotoxicity. [17][18][19] Alpinetin (7-hydroxy-5-methoxyflavanone) is a natural flavonoid isolated from the seeds of Alpinia katsumadai Hayata. Alpinetin has anti-inflammatory and antioxidative activities, and it is commonly used in traditional Chinese medicine for therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that Hyp was able to downregulate PHLPP2 expression, induce AKT phosphorylation and inactivate GSK-3β, and thereby, promoted Nrf2 nuclear translocation. 15 Hyp could enhance the cellular antioxidant defense system through Nrf2 signaling pathway to upregulate HO-1 expression. In this study, we further dissect the mechanism that Hyp control Bach1 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that Hyp attenuates H 2 O 2 -induced hepatic L02 cell oxidative damage via MAPK-dependent Keap1-Nrf2-ARE signaling pathway to upregulate HO-1 expression and enhance intracellular antioxidant activity, and Hyp could protect against oxidative stress-induced liver injury by regulating the PHLPP2-AKT-GSK-3β signaling pathway in vivo and in vitro. 14 , 15 However, rarely research reports the effect of Hyp on the oxidative liver injury model animal. The influence of Hyp on the expression and distribution of Bach1, and the relationship of Hyp’s antioxidative effect and the influence of Bach1 remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperoside is a major pharmacologically active component in A. esculentus . Many studies have already shown that hyperoside has pharmacological effects, such as relieving oxidative stress injury in cells and anticancer properties 13 15 .…”
Section: Introductionmentioning
confidence: 99%